2018
DOI: 10.1016/j.cmet.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Adipogenesis Induced by β3-Adrenergic Receptor Activation with Single-Cell Expression Profiling

Abstract: Recruitment of brown/beige adipocytes (BAs) in white adipose tissue (WAT) involves proliferation and differentiation of adipocyte stem cells (ASCs) in concert with close interactions with resident immune cells. To deconvolve stromal cell heterogeneity in a comprehensive and unbiased fashion, we performed single-cell RNA sequencing (scRNA-seq) of >33,000 stromal/vascular cells from epididymal WAT (eWAT) and inguinal WAT (iWAT) under control conditions and during β3-adrenergic receptor (ADRB3) activation. scRNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
316
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(345 citation statements)
references
References 39 publications
27
316
1
1
Order By: Relevance
“…Another way to model the negative energy balance associated with weight loss is via activating lipolysis. Dr Granneman et al per-formed scRNA-seq on over 33 000 cells from the stromal vascular fraction of epididymal and inguinal AT in lean mice with or without β-adrenergic stimulation 86. The purpose of this study was to evaluate the recruitment of brown/beige adipocytes during lipolytic stimulation, and they indeed found that they could classify a proliferating population of cells that would differentiate into brown/ beige adipocytes.…”
mentioning
confidence: 93%
“…Another way to model the negative energy balance associated with weight loss is via activating lipolysis. Dr Granneman et al per-formed scRNA-seq on over 33 000 cells from the stromal vascular fraction of epididymal and inguinal AT in lean mice with or without β-adrenergic stimulation 86. The purpose of this study was to evaluate the recruitment of brown/beige adipocytes during lipolytic stimulation, and they indeed found that they could classify a proliferating population of cells that would differentiate into brown/ beige adipocytes.…”
mentioning
confidence: 93%
“…Recent advances in the ability to study single-cell transcriptomes can be leveraged to better understand the cellular composition of adipose tissue [11][12][13]. Single-cell transcriptomics of nonmature adipocytes in mouse fat has revealed specific populations of adipocyte stem cells primed to expand in response to adrenergic stimulation [13], stromal cells capable of inhibiting adipogenesis [11], and cells with enhanced adipogenic or fibro-inflammatory properties [14]. The use of single-cell transcriptomics to define mature adipocyte subtypes is complicated by the large size and high buoyancy of these cells, and the fact that the extensive proteolytic digestion required to isolate them from the adipose tissue compromises their viability and alters their phenotype [15].…”
Section: Introductionmentioning
confidence: 99%
“…PGT mRNA in iWAT is expressed in an adipocyte precursor population 63 . This cell specificity would position PGT for paracrine control 7 of white or beige adipogenesis.…”
Section: Discussionmentioning
confidence: 99%